2003
DOI: 10.4049/jimmunol.170.1.413
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mouse MD-2 Residues Important for Forming the Cell Surface TLR4-MD-2 Complex Recognized by Anti-TLR4-MD-2 Antibodies, and for Conferring LPS and Taxol Responsiveness on Mouse TLR4 by Alanine-Scanning Mutagenesis

Abstract: The expression of MD-2, which associates with Toll-like receptor (TLR) 4 on the cell surface, confers LPS and LPS-mimetic Taxol responsiveness on TLR4. Alanine-scanning mutagenesis was performed to identify the mouse MD-2 residues important for conferring LPS and Taxol responsiveness on mouse TLR4, and for forming the cell surface TLR4-MD-2 complex recognized by anti-TLR4-MD-2 Ab MTS510. Single alanine mutations were introduced into mouse MD-2 (residues 17–160), and the mutants were expressed in a human cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 34 publications
10
59
0
Order By: Relevance
“…At pharmacologically low concentrations (exemplified by 1 mM in this study), the JNK signaling pathway was the major stimulator of IL-6 gene regulation. However, at suprapharmacologically high concentrations (exemplified by 50 mM in this study), paclitaxel exerted LPS-like effects likely through the TLR4 signaling pathway as reported previously (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001). Elucidation of the signaling networks that are differentially initiated by low concentrations or by high concentrations of paclitaxel and the verification of specific inhibitors against key molecules inside the networks may help us in developing a better chemotherapeutic strategy in treatment of ovarian cancer with paclitaxel.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…At pharmacologically low concentrations (exemplified by 1 mM in this study), the JNK signaling pathway was the major stimulator of IL-6 gene regulation. However, at suprapharmacologically high concentrations (exemplified by 50 mM in this study), paclitaxel exerted LPS-like effects likely through the TLR4 signaling pathway as reported previously (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001). Elucidation of the signaling networks that are differentially initiated by low concentrations or by high concentrations of paclitaxel and the verification of specific inhibitors against key molecules inside the networks may help us in developing a better chemotherapeutic strategy in treatment of ovarian cancer with paclitaxel.…”
Section: Discussionsupporting
confidence: 72%
“…Taken together, these results indicated that two pathways ( Figure 7) are involved in the upregulation of IL-6 by treatment with paclitaxel: (a) at low, pharmacological concentrations (exemplified by 1 mM in this study), the JNK signaling pathway was the major stimulator of IL-6 gene regulation, and (b) at high, suprapharmacological concentrations (exemplified by 50 mM in this study), paclitaxel exerted LPS-like effects, which were most likely carried out through the TLR4 signaling pathway as reported previously (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001). …”
Section: Sp600125supporting
confidence: 74%
See 3 more Smart Citations